Orbital perturbations using geopotential coefficients up to high degree and order: Highly eccentric orbits - De Moraes, Rodolpho Vilhena [UNESP]; Wnuk, Edwin (My University, 1998)
Several methods have been proposed for calculations of the eccentricity function for a high value of the eccentricity, however they cannot be used when the high degree and order coefficients of gravity fields are taken into account. The method proposed by Wnuk1 is numerically stable in this case, but when is used, a large number of terms occurs in formulas for geopotential perturbations. In this paper we propose an application of expansions of some functions of the eccentric anomaly E as well as Hansen coefficients in power series of (e - e*), where e* is a fixed value of the eccentricity derived by Da Silva Fernandes2,3,4. These series are convergent for all e < 1.